Introduction to mass communication : - Banran, Stanley J, (Mc GrawHill, 2006)
This text emphasizes that media audiences can take more active roles as media consumers and have a deeper understanding of the influence the media have in both shaping and reflecting culture. Through this cultural perspective, students learn that audience members are as much a part of the mass communication process as are the media producers, technologies, and industries. --This text refers to an out of print or unavailable edition of this title.